The Role of Parents in Overcoming the Impact of Gadget Use on the Social Development of Children Aged 3–4 Years - Adinda Putri Ramadhan; Atin Fatimah; Dian Surya Apriliyanti (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study aims to describe the role of parents in addressing the impact of gadget use on the social development of children aged 3–4 years. Using a qualitative descriptive approach, the study was conducted in Kampung Masjid RT02/RW03, Ciputat District, South Tangerang City. Data were collected through observation and semi-structured interviews with two parents. The findings indicate that parents are aware of the importance of accompanying and supervising their children's gadget use. Although the children showed early signs of dependency on gadgets, parents attempted to address this by limiting screen time and offering alternative educational and social activities. Uncontrolled gadget use can hinder children's social interaction, but with proper supervision, it may enhance language and communication skills. The study concludes that active parental involvement is essential to ensure that gadget use does not impede the social development of early childhood.